Is the co-location of GPs in primary care centres associated with a higher patient satisfaction? Evidence from a population survey in Italy - Manila Bonciani; Sara Barsanti; Anna Maria Murante (BMC, 2017)
Abstract Background Several countries have co-located General Practitioners (GPs) in Primary Care Centres (PCCs) with other health and social care professionals in order to improve integrated care. It is not clear whether the co-location of a multidisciplinary team actually facilitates a positive patient experience concerning GP care. The aim of this study was to verify whether the co-location of GPs in PCCs is associated positively with patient satisfaction with their GP when patients have experience of a multidisciplinary team. We also investigated whether patients who frequently use health services, due to their complex needs, benefitted the most from the co-location of a multidisciplinary team. Methods The study used data from a population survey carried out in Tuscany (central Italy) at the beginning of 2015 to evaluate the patients' experience and satisfaction with their GPs. Multilevel linear regression models were implemented to verify the relationship between patient satisfaction and co-location. This key explanatory variable was measured by considering both the list of GPs working in PCCs and the answers of surveyed patients who had experienced the co-location of their GP in a multidisciplinary team. We also explored the effect modification on patient satisfaction due to the use of hospitalisation, access to emergency departments and visits with specialists, by performing the multilevel modelling on two strata of patient data: frequent and non-frequent health service users. Results A sample of 2025 GP patients were included in the study, 757 of which were patients of GPs working in a PCC. Patient satisfaction with their GP was generally positive. Results showed that having a GP working within a PCC and the experience of the co-located multidisciplinary team were associated with a higher satisfaction (p < 0.01). For non-frequent users of health services on the other hand, the co-location of multidisciplinary team in PCCs was not significantly associated with patient satisfaction, whereas for frequent users, the strength of relationships identified in the overall model increased (p < 0.01). Conclusion The co-location of GPs with other professionals and their joint working as experienced in PCCs seems to represent a greater benefit for patients, especially for those with complex needs who use primary care, hospitals, emergency care and specialized care frequently.